2007
DOI: 10.1104/pp.107.106278
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Phytosterol Esters: Identification of a Sterol O-Acyltransferase in Arabidopsis

Abstract: Fatty acyl esters of phytosterols are a major form of sterol conjugates distributed in many parts of plants. In this study we report an Arabidopsis (Arabidopsis thaliana) gene, AtSAT1 (At3g51970), which encodes for a novel sterol O-acyltransferase. When expressed in yeast (Saccharomyces cerevisiae), AtSAT1 mediated production of sterol esters enriched with lanosterol. Enzyme property assessment using cell-free lysate of yeast expressing AtSAT1 suggested the enzyme preferred cycloartenol as acyl acceptor and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 55 publications
(58 reference statements)
5
51
0
Order By: Relevance
“…In this study, FA profiles (particularly 16:0-and 18:0-FAs) were significantly altered in mutants and OEs of SMO1-1 and ACBP1 (Table I). As 16:0-and 18:0-FAs were the two major species elevated in Arabidopsis OEs of acyl-CoA:sterol acyltransferase with substrate specificity for 16:0-and 18:0-CoA esters (Chen et al, 2007), our results suggest a regulatory role for ACBP1 in sterol acylation via its association with these acyl-CoA species. Deviations of 16:1-and 16:3-FA levels in mutants and OEs of SMO1-1 and ACBP1 also revealed a compositional change in plastidial lipids (Table I).…”
Section: Acbp1 Links Fa Homeostasis To Sterol Productionmentioning
confidence: 55%
“…In this study, FA profiles (particularly 16:0-and 18:0-FAs) were significantly altered in mutants and OEs of SMO1-1 and ACBP1 (Table I). As 16:0-and 18:0-FAs were the two major species elevated in Arabidopsis OEs of acyl-CoA:sterol acyltransferase with substrate specificity for 16:0-and 18:0-CoA esters (Chen et al, 2007), our results suggest a regulatory role for ACBP1 in sterol acylation via its association with these acyl-CoA species. Deviations of 16:1-and 16:3-FA levels in mutants and OEs of SMO1-1 and ACBP1 also revealed a compositional change in plastidial lipids (Table I).…”
Section: Acbp1 Links Fa Homeostasis To Sterol Productionmentioning
confidence: 55%
“…PSAT1 catalyzes a phospholipid-dependent (acyl-CoA-independent) formation of SE (Banas et al, 2005). Recently, Chen et al (2007) demonstrated the involvement of ASAT1, an acylCoA:sterol acyltransferase, in sterol esterification by expressing the corresponding gene both in yeast and in planta, where they showed that the SE content of Arabidopsis seeds expressing an ASAT1 cDNA driven by a NAPIN promoter was about 2-fold higher than that of wild-type seeds. We performed here a detailed analysis of the SE content of psat1-1, psat1-2, and asat1-1 deficient mutant lines.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme was shown to prefer saturated fatty acyl-CoAs as acyl donors and cycloartenol as the acyl acceptor. Overexpression of AtASAT1 in seeds of Arabidopsis resulted in a strong accumulation of cycloartenol fatty acyl esters accompanied by an increase of the whole SE content of these seeds and, in spite of a slight decrease of the free sterol pool, an increase of the total sterol content of the transgenic seeds by up to 60% compared with that of the wild type (Chen et al, 2007). We took advantage of the availability of Arabidopsis T-DNA insertion mutants of these two genes to investigate their respective physiological roles.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Fatty acid acylation of phytosterol can be catalyzed by CoA-dependent enzymes. Recently a plant gene, acyl-CoA:sterol acyltransferase, catalyzing the acyl-CoA-dependent acylation of phytosterol was identified (Chen et al, 2007). The enzyme has a preference for palmitoyl-CoA as acyl donor and cycloartenol as acyl acceptor, however, end product phytosterols, such as sitosterol, were also acylated.…”
Section: Sterolsmentioning
confidence: 99%